2022
DOI: 10.2478/bsrj-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization in Teaching Economic Disciplines: Past, Current and Future Perspectives

Abstract: This special issue of Business Systems Research (SI of the BSR) highlights the past, current and future perspectives of digitalization in teaching economic disciplines. The emphasis has been put on digital competencies, the quality of e-learning, e-exams, digital tools, gamification, and digital and mobile technologies used in the teaching process in the field of economics. The main focus groups of the research are teachers and students from the economic field of education at both university and secondary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the field of economic education, there is interest in m-learning at the university level [3,42,44,121,122], but very little attention has been given to secondary education, particularly in the post-pandemic period after returning to classrooms. Previous cross-country study (Poland, Croatia, Serbia) [2], addresses the topic of economic education through e-learning at the high school level, and this present research can contribute to the development of knowledge from a broader perspective, expanding the scope of observation to obtain a more comprehensive understanding of students' attitudes towards m-learning.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In the field of economic education, there is interest in m-learning at the university level [3,42,44,121,122], but very little attention has been given to secondary education, particularly in the post-pandemic period after returning to classrooms. Previous cross-country study (Poland, Croatia, Serbia) [2], addresses the topic of economic education through e-learning at the high school level, and this present research can contribute to the development of knowledge from a broader perspective, expanding the scope of observation to obtain a more comprehensive understanding of students' attitudes towards m-learning.…”
Section: Discussionmentioning
confidence: 84%
“…The unexpected social isolation brought students and teachers to the situation of connecting through the mobile devices, the transition to remote teaching being realized suddenly and in an unplanned manner [13]. With regard to the education systems in the central-eastern part of Europe, which includes the present study as well, the research carried out during and after the pandemic, in different countries, highlighted the relatively common elements regarding the advantages and disadvantages of m-learning [2]. A research conducted in Romania identified several benefits such as program flexibility, adaptation to diverse learning styles, and access to numerous useful digital tools.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…During the COVID-19 pandemic, e-learning supported the abilities of students, academic staff, and professionals to develop professionally and personally [18][19][20]. Most higher education institutions offered online courses to students both on and off campus during the pandemic, and some have continued this practice [21,22].…”
Section: E-learning During the Covid-19 Eramentioning
confidence: 99%